The Effect of Religiosity and Rationalization on Fraud on the Quality of Financial Reports - Astri Paramitajaya, Naj’ma; Rosy Rochmatullah, Mahameru (Research Horizon, 2025)
This study aims to examine the effect of religiosity and rationalization on the quality of financial reports. The research uses a quantitative approach with primary data collected through questionnaires. The population consists of 28 villages located in Baki District and Gatak District, Sukoharjo Regency. The sampling technique used is purposive sampling, resulting in 100 respondents who are village officials. Data analysis was carried out using Multiple Linear Regression Analysis. The results show that the religiosity variable has a significant influence on the quality of financial reports, indicating that the higher the level of religiosity among village officials, the better the quality of the financial reports produced. On the other hand, the rationalization variable does not have a significant influence on the quality of financial reports, meaning that the tendency of individuals to justify inappropriate actions does not have a real effect on the quality of financial reporting. These findings emphasize the importance of religious values in maintaining accountability and integrity in public sector financial reporting.